Biting the Hand that Feeds: Reconsidering Partisanship in an Age of Permanent Austerity - Abel Bojar (London School of Economics and Political Science (LSE), European Institute, 2015)
The New Politics of the welfare state suggests that periods of welfare retrenchment present policy-makers with a qualitatively different set of challenges and electoral incentives compared to periods of welfare expansion. An unresolved puzzle for this literature is the relative electoral success of retrenching governments in recent decades, as evidenced by various studies on fiscal consolidations. This article points to the importance of partisan biases as the main explanatory factor. I argue that partisan biases in the electorate create incentives for incumbent governments to depart from their representative function and push the burden of retrenchment on the very constituencies that they owe their electoral mandate to ("Nixon-goes-to-China"). After offering a simple model on the logic of partisan biases, the article proceeds by testing the unexpected partisan hypotheses that the model generates. My findings from a cross-section-time-series analysis in a set of 25 OECD countries provide corroborative evidence on this Nixon-goes-to-China logic of welfare retrenchment: governments systematically inflict pain on their core constituencies. Some of the losses that the core constituencies suffer during austerity, however, are recouped during fiscal expansions when traditional partisan patterns take hold.
Keywords: 330; welfare retrenchment; social spending; austerity; partisanship; Nixon-goes-to-China; representation